Acute hypoxia induced dysregulation of clock-controlled ovary functions - Ding, Mengnan; Lu, Yarong; Huang, Xin; Xing, Chen; Hou, Shaojun; Wang, Dongxue; Zhang, Yifan; Wang, Wei; Zhang, Chongchong; Zhang, Min; Meng, Fanfei; Liu, Kun; et al. (Frontiers in Physiology, 2022)
High altitudes or exposure to hypoxia leads to female reproductive disorders. Circadian clocks are intrinsic time-tracking systems that enable organisms to adapt to the Earth’s 24-h light/dark cycle, which can be entrained by other environmental stimuli to regulate physiological and pathological responses. In this study, we focused on whether ovarian circadian clock proteins were involved in regulating female reproductive dysfunction under hypoxic conditions. Hypobaric hypoxia was found to induce a significantly prolonged estrous cycle in female mice, accompanied by follicular atresia, pituitary/ovarian hormone synthesis disorder, and decreased LHCGR expression in the ovaries. Under the same conditions, the levels of the ovarian circadian clock proteins, CLOCK and BMAL1, were suppressed, whereas E4BP4 levels were upregulated. Results from granulosa cells (GCs) further demonstrated that CLOCK: BMAL1 and E4BP4 function as transcriptional activators and repressor of LHCGR in ovarain GCs, respectively, which responses were mediated by HIF1ɑ-dependent (E4BP4 upregulation) and independent (CLOCK and BMAL1 downregulation) manners. The LHCGR agonist was shown to efficiently recover the impairment of ovulation-related gene (EREG and PGR) expression in GCs induced by hypoxia. We conclude that hypoxia exposure causes dysregulation of ovarian circadian clock protein (CLOCK, BMAL1, E4BP4) expression, which mediates female reproductive dysfunction by impairing LHCGR-dependent signaling events. Adjusting the timing system or recovering the LHCGR level in the ovaries may be helpful in overcoming female reproductive disorders occurring in the highlands.